Association between nausea and vomiting of pregnancy and postpartum depression: the Japan Environment and Children's Study. (2nd January 2022) - Muchanga, Sifa Marie Joelle; Eitoku, Masamitsu; Mbelambela, Etongola Papy; Ninomiya, Hitoshi; Iiyama, Tatsuo; Komori, Kaori; Yasumitsu-Lovell, Kahoko; Mitsuda, Naomi; Tozin, Rahma Rashid; Maeda, Nagamasa; Fujieda, Mikiya; Suganuma, Narufumi; et al.
Abstract: Objective: Postpartum depression (PPD) is a global emotional distress that affects women and their offspring regardless of their culture. The association between nausea and vomiting of pregnancy (NVP) and PPD has been widely described only for the severe form of NVP. We aimed to assess the relationship between PPD and NVP with regards to its severity. Methods: Data from the Japan Environment and Children's Study (JECS), a birth cohort study, were analyzed. PPD was assessed using the Edinburgh Postnatal Depression Scale (EPDS). Multiple logistic regression models were performed to assess the association between NVP and PPD. Results: Out of the 80, 396 women included in the study 14% had PPD. Among them 4, 640 (42.1%) had mild NVP; 3, 295 (29.9%) had moderate NVP whereas 1, 481 (13.4%) had severe NVP. All forms of NVP were associated with PPD and the association gradually increased with the severity of NVP symptoms with odd ratio (OR): 1.26; 95% confidence interval (CI): 1.18–1.35 for mild, OR: 1.28; 95% CI: 1.19–1.38 for moderate and OR: 1.54; 95% CI: 1.42–1.68 for severe NVP. Conclusion: Japanese women with NVP were more susceptible to develop PPD and the more severe the NVP symptoms were, the greater the risk of PPD. Thus, close monitoring of NVP-affected women is recommended.